2014
DOI: 10.3349/ymj.2014.55.1.254
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Social Factors Affecting Internet Searches on Suicide in Korea: A Big Data Analysis of Google Search Trends

Abstract: PurposeThe average mortality rate for death by suicide among OECD countries is 12.8 per 100000, and 33.5 for Korea. The present study analyzed big data extracted from Google to identify factors related to searches on suicide in Korea.Materials and MethodsGoogle search trends for the search words of suicide, stress, exercise, and drinking were obtained for 2004-2010. Analyzing data by month, the relationship between the actual number of suicides and search words per year was examined using multi-level models.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…It is essential that the key functions of data processing are supported by the applications of big data [13]. Big data applications should be user-friendly, transparent, and menu-driven [13,14]. The majority of data in health care is unstructured, such as from natural language processing [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is essential that the key functions of data processing are supported by the applications of big data [13]. Big data applications should be user-friendly, transparent, and menu-driven [13,14]. The majority of data in health care is unstructured, such as from natural language processing [12].…”
Section: Resultsmentioning
confidence: 99%
“…Once data is generated, the costs associated with securing and storing them remain high [25]. Costs are also incurred with transferring data from one place to another as well as analyzing it [14,21,22]. Some researchers have been able to combine the themes of Data structure and Storage and transfers when they illustrate how structured data can be easily stored, queried, analyzed, and so forth, but unstructured data is not as easily manipulated [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study has reported that children feel unhappy when parents smoke at home (Chen et al 2015a). In addition, this stress is considered a risk factor for suicide, especially in Korea which has the highest suicide rate among Organization for Economic Cooperation and Development (OECD) countries (Song et al 2014). Third, secondhand smoking is associated with other mental disorders besides depression and stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stress is proposed as a major risk factor for suicide. This is especially important in Korea, which has the highest suicide rate among the Organization for Economic Cooperation and Development countries [26,27,28]. Past traumatic experiences cause increased actual vulnerability among elders, as most elders experience physical, psychological, and social changes related with health problems, decreased economic status, and loneliness, all of which cause stress [29].…”
Section: Introductionmentioning
confidence: 99%